2012
DOI: 10.4236/ojfd.2012.24a042
|View full text |Cite
|
Sign up to set email alerts
|

Study of Interaction between Supersonic Flow and Rods or Jets Surrounded by Porous Cavity

Abstract: In this experiment, the effects of the combination of jets or rods and a porous cavity on the supersonic flow field are studied by means of visualization of schlieren method and the measurements of wall static pressures and the flow direction in the cavity with the thermal tuft probe. Three cases of jets or rods arrangements are tested in the experiments. As a result, a bow shock wave which is generated by the jets or rods is observed by mean of schlieren method. And it is confirmed that the expansion region a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Figure 5 shows the starting shock wave positions on the lower wall for 000, 010, 030 and 111. In this figure, previous results reported by authors 9,10) are shown as a reference. Dashed lines indicate a start and an end of the cavity.…”
Section: Pe_31mentioning
confidence: 80%
See 1 more Smart Citation
“…Figure 5 shows the starting shock wave positions on the lower wall for 000, 010, 030 and 111. In this figure, previous results reported by authors 9,10) are shown as a reference. Dashed lines indicate a start and an end of the cavity.…”
Section: Pe_31mentioning
confidence: 80%
“…The flow in the cavity is spouted again, achieving small fine injections through many small porous holes. Using the device, we already evaluated the effect of the combination of porous cavity and the rods or jets on the flow 8,9) . Accordingly the flow direction is affected not only by the rods and jets also by the relative position of the starting shock wave to the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…This flow field has experimentally investigated with Schlieren method, pressure measurements, and a thermal tuft probe which can detect flow directions. [9][10][11][12] As a result, it is found that the cavity flow is affected by the jets arrangements, which concerns the three dimensional structure of the bow shock wave. In the experiments, it is difficult to clarify the detailed three-dimensional flow around the cavity and the circulation between the main flow and the cavity flow at the same time.…”
Section: Introductionmentioning
confidence: 99%